World Bank Research Digest, Vol. 1(1) - World Bank (Washington, DC, 2014)
In this issue: money for nothing: the dire straits of medical practice in Delhi, India; World Bank research digest: an effective way to disseminate research findings; bank supervision and corruption in lending; who benefits from residential water and electricity subsidies? Child labor and agriculture shocks; market access for sale; and public disclosure: a tool for controlling pollution.